2015
DOI: 10.1093/cje/bev017
|View full text |Cite
|
Sign up to set email alerts
|

Keynes and the interwar commodity option markets

Abstract: In the first quarter of the twentieth century, options began to be widely employed in the main financial centres in Europe and the USA for trading in spot and futures markets. From 1921 onward, Keynes embarked upon investment in these derivatives mainly-but not exclusively-in the commodity markets, showing a true fascination for this method of speculation. This type of financial investment he pursued mainly in the 1920s, with only a few operations undertaken during the 1930s. The option markets in which Keynes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Rupert Trouton worked with Keynes for the Government during the First World War, was his student at Cambridge, and had a lot of dealings with him when he was at Buckmaster & Moore and Laurence, Keen & Gardner, which were King's main broker firms. It was Trouton who, in 1921, introduced Keynes to metal options (Marcuzzo and Sanfilippo 2016). He was a cofounder with Keynes and Falk of the AD Investment Trust and the P.R.…”
Section: Keynes's Main Advisorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rupert Trouton worked with Keynes for the Government during the First World War, was his student at Cambridge, and had a lot of dealings with him when he was at Buckmaster & Moore and Laurence, Keen & Gardner, which were King's main broker firms. It was Trouton who, in 1921, introduced Keynes to metal options (Marcuzzo and Sanfilippo 2016). He was a cofounder with Keynes and Falk of the AD Investment Trust and the P.R.…”
Section: Keynes's Main Advisorsmentioning
confidence: 99%
“…It is a well-established fact that, by this time, Keynes had decidedly shifted to the kind of buy-and-hold approach that is well exemplified in his college administration, and that Keynes based this strategy on limited diversification and a highly idiosyncratic selection of a restricted set of shares. Also, Marcuzzo and Sanfilippo (2016) found that Keynes basically gave up his dealings in options in the early 1930s, which can also be interpreted as a break in his style of investment. Less clear is why, and exactly when, Keynes changed his mind, and how the new stock-market strategy relates to the parallel investment in commodity and exchange markets.…”
Section: Developments and Changes In Keynes's Investment Philosophy Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Marcuzzo and Sanfilippo, ‘Keynes’; Fantacci, Marcuzzo, and Sanfilippo, ‘Speculation in commodities’; Cavalli and Christiano, ‘Keynes’ speculation’.…”
mentioning
confidence: 99%